Immaterieller Schadensersatz und der Wandel völkerrechtlicher Privatrechtsanalogien - Stendel, Robert Christoph (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2023)
The study offers a comprehensive analysis of non-material damages in public international law enriched by historical, empirical, and sociological perspectives. Individual chapters examine how inter-state international law, the three major regional human rights systems (ECHR, IACHR, AfCHPR), and international investment law deal with those damages. These chapters are linked to the overarching issue of whether international law's profound changes affected its private law heritage. As an analytical framework, the study employs the distinction between private and public law. Additionally, it offers insights into the national biases stemming from international law's reception of private law and the resulting problems for its application.